Real-time PCR assay for detecting illicit steroid administration in veal calves allows reliable biomarker profiling of formalin-fixed, paraffin-embedded (FFPE) archival tissue samples. (15th May 2020) - Benedetto, Alessandro; Pezzolato, Marzia; Beltramo, Chiara; Audino, Valentina; Ingravalle, Francesco; Pillitteri, Caterina; Foschini, Stefano; Peletto, Simone; Bozzetta, Elena
Highlights: An available assay to detect sex-steroids abuse in calves was modified to work on FFPE. Method validation was carried out on FFPE archive blocks from experimental trials. A RT-qPCR comparative study of FFPE and RNAlater field samples was performed. The modified assay may overcome the limitations of field sampling at slaughterhouse. Abstract: In the context of mRNA biomarker profiling, formalin fixed paraffin embedded (FFPE) samples represent an interesting source for retrospective analysis. However, the implementation in routine analysis of FFPE samples, following legislation demands for validated and accredited methods, often requires critical revision and optimization. In the frame of an official control program the validation study of a molecular test for detection of sex steroids administration in calves, based on quantification of progesterone-Receptor mRNA in bulbo-urethral gland samples, was performed: analyses were made on FFPE tissues sections routinary used for histological investigations and compared with RNAlater tissue preservation. To overcome the limitations of original assays several modifications were tested. Obtained results confirmed how Progesterone-Receptor assay represent a useful tool to study suspected cases of sex steroid illicit administration in veal calves, complementary to histological and/or immune histochemical investigation, overcoming the limitation of field studies, where optimal pre-analytical condition cannot always be guarantee.